Self-Health Literacy Among Students in Islamic School Science Education: A Comparative Analysis Across Gender, Grade Level, and School Context - Annisa Nur Khasanah; Dadan Rosana; Insih Wilujeng; Arifin Septiyanto (Bumi Publikasi Nusantara, 2027)
This study explores students’ self-health literacy within Islamic school science education by examining differences across gender, grade level, and school context. Using a cross-sectional survey approach, data were collected from junior high school students through an instrument grounded in the health literacy framework, encompassing access, understanding, processing, and application of health information. Students generally demonstrate a positive level of self-health literacy, with stronger performance in applying health knowledge compared to evaluating information critically. Relationships among all dimensions were found to be interconnected, highlighting the integrative nature of health literacy development. No significant differences emerged across gender and school context, while variations in information access were observed across grade levels. The study underscores the importance of integrating digital literacy and value-based education in strengthening students’ health literacy.